Pediatric cervical neurofibroma. A case report - Oré Acevedo, Juan Francisco (2016)
Neurofibromas are benign tumors of frequent presentation in the head and neck. We report the case of a 14 years old male who presented a cervical tumor 14 cm in length. Despite the size of the tumor and the fact that it displaced the cervical midline structures, the patient remained asymptomatic. The pathology report following surgery was of a neurofibroma. On discharge there were no motor limitations present, but loss of soft palate sensitivity and nauseous reflex, and the previous Horner syndrome. Surgery is the gold standard treatment and total resection is ideal, but debulking is preferred according to the neurofibroma characteristics. Neurological deficit could be expected.